Application of next-generation sequencing in clinical oncology to advance personalized treatment of cancer - Guan, Yan-Fang; Li, Gai-Rui; Wang, Rong-Jiao; Yi, Yu-Ting; Yang, Ling; Jiang, Dan; Zhang, Xiao-Ping; Peng, Yin (Ai zheng, 2012)
With the development and improvement of new sequencing technology, next-generation sequencing （NGS） has been applied increasingly ~n cancer genomics research over the past decade. More recently, NGS has been adopted in clinical oncology to advance personalized treatment of cancer. NGS is used to identify novel and rare cancer mutations, detect familial cancer mutation carriers, and provide molecular rationale for appropriate targeted therapy. Compared to traditional sequencing, NGS holds many advantages, such as the ability to fully sequence all types of mutations for a large number of genes （hundreds to thousands） in a single test at a relatively low cost. However, significant challenges, particularly with respect to the requirement for simpler assays, more flexible throughput, shorter turnaround time, and most importantly, easier data analysis and interpretation, will have to be overcome to translate NGS to the bedside of cancer patients. Overall, continuous dedication to apply NGS in clinical oncology practice will enable us to be one step closer to personalized medicine.